The Effect of Health Education Using A Pocket Book About Hepatitis B on The Knowledge of Prospective Brides - Siwi Yuni Purnamasari; Desy Rosita; Oon Fatonah (MEDICA (International Medical Scientific Journal), 2025)
Hepatitis, an inflammation of the liver caused by a virus, accounts for 1.1 million deaths globally each year, with 96% caused by hepatitis B and C. The National Program prioritizes the Prevention of Mother-to-Child Transmission (PPIA), as 95% of hepatitis B transmissions occur vertically. Health education, which aims to change unhealthy behaviors, is more effective when supported by educational media such as pocket books, which are small, informative, visually appealing, and easy to carry, allowing individuals to access the material anytime. This study aimed to analyze the effect of health education using pocket books on Hepatitis B knowledge among brides-to-be at the Pahauman Community Health Center in Landak District. A quasi-experimental design with a pre-post test without a control group was employed, involving 31 female brides-to-be selected through total sampling. Participants received health education via pocket books, and their knowledge of Hepatitis B was assessed before and after the intervention. The results showed that after the intervention, the average knowledge score was 93.10, with a median of 90 and a standard deviation of 6.231, ranging from 80 to 100. Statistical analysis demonstrated a significant improvement in knowledge, with a p-value of 0.000 (p<0.05). In conclusion, health education using pocket books significantly enhanced the knowledge of prospective brides regarding Hepatitis B at the Pahauman Community Health Center in Landak District.